Shortfalls in the global protected area network at representing marine biodiversity - Klein, Carissa J. (Sci Rep, 2015)
The first international goal for establishing marine protected areas (MPAs) to conserve the ocean’s biodiversity was set in 2002. Since 2006, the Convention on Biological Diversity (CBD) has driven MPA establishment, with 193 parties committed to protecting >10% of marine environments globally by 2020, especially ‘areas of particular importance for biodiversity’ (Aichi target 11). This has resulted in nearly 10 million km(2) of new MPAs, a growth of ~360% in a decade. Unlike on land, it is not known how well protected areas capture marine biodiversity, leaving a significant gap in our understanding of existing MPAs and future protection requirements. We assess the overlap of global MPAs with the ranges of 17,348 marine species (fishes, mammals, invertebrates), and find that 97.4% of species have <10% of their ranges represented in stricter conservation classes. Almost all (99.8%) of the very poorly represented species (<2% coverage) are found within exclusive economic zones, suggesting an important role for particular nations to better protect biodiversity. Our results offer strategic guidance on where MPAs should be placed to support the CBD’s overall goal to avert biodiversity loss. Achieving this goal is imperative for nature and humanity, as people depend on biodiversity for important and valuable services.